A Reverse Shoulder Arthroplasty Implantation With Custom-Made Humerus and Intraoperative GPS Navigation in a Rare Case of Unilateral Hip and Shoulder Dysplasia Associated With a Bone Marrow Mosaic Truncating Variant: Case Report - Giovanni Battista Colasanti , MD; Elisa Troiano , MD; Alice Giulia De Sensi , MD; Laura Di Sarno PhD; Alessandra Renieri , MD, PhD; Nicola Mondanelli , MD, PhD; Sefano Giannotti , MD, PhD (Journal of Shoulder and Elbow Arthroplasty, 2023)
Joint dysplasias always represent a great challenge for prosthetic surgeons. The common altered anatomical landmarks and the subversion of the anatomy of soft tissues surrounding the dysplastic joint are problems that can cause difficulties if approached with standard methods. Together with the resolution of functional issues related to dysplasia, the understanding of the underlying cause is fundamental. DNA analysis is generally performed via blood sampling; however, this might lead to misdiagnosis in case mosaicism is not detected in blood components. The etiology of genetic diseases can be further examined by means of whole exome sequencing and the detection of somatic mosaicism, recognized as a fundamental contributor to genetic diseases themselves. In this study, the clinical case of a patient suffering from a rare unilateral dysplasia localized to the left coxo-femoral and glenohumeral joint and treated at our center for reverse shoulder arthroplasty is reported. By virtue of the glenohumeral anatomical peculiarities, we had to devise a hybrid custom-made and navigated approach by means of a custom-made prosthetic stem and dedicated patient-specific instrumentation, using intraoperative GPS navigation for glenoid prosthesis. In addition, a genetic study was conducted on intraoperatively harvested bone marrow, which proved to be crucial in understanding the epigenetic basis of dysplasia. In fact, the patient resulted negative in blood but positive for a truncating variant of PTEN c.781C > T (p.(Gln261 *)) in 12% of the sequence analyzed in the bone marrow.